Sources of evidence in HIV/AIDS care: pilot study comparing family physicians and AIDS service organization staff - Upshur Ross EG; Tracy C Shawn; Stefanski Kasia E (BMC, 2004)
Abstract Background The improvement of the quality of the evidence used in treatment decision-making is especially important in the case of patients with complicated disease processes such as HIV/AIDS for which multiple treatment strategies exist with conflicting reports of efficacy. Little is known about the perceptions of distinct groups of health care workers regarding various sources of evidence and how these influence the clinical decision-making process. Our objective was to investigate how two groups of treatment information providers for people living with HIV/AIDS perceive the importance of various sources of treatment information. Methods Surveys were distributed to staff at two local AIDS service organizations and to family physicians at three community health centres treating people living with HIV/AIDS. Participants were asked to rate the importance of 10 different sources of evidence for HIV/AIDS treatment information on a 5-point Likert-type scale. Mean rating scores and relative rankings were compared. Results Findings suggest that a discordance exists between the two health information provider groups in terms of their perceptions of the various sources of evidence. Furthermore, AIDS service organization staff ranked health care professionals as the most important source of information whereas physicians deemed AIDS service organizations to be relatively unimportant. The two groups appear to share a common mistrust for information from pharmaceutical industries. Conclusions Discordance exists between medical "experts" from different backgrounds relating to their perceptions of evidence. Further investigation is warranted in order to reveal any effects on the quality of treatment information and implications in the decision-making process. Possible effects on collaboration and working relationships also warrant further exploration.